Pendampingan Pastoral Terhadap Remaja Korban Perceraian di Jemaat GMIM Kerajaan Allah Lolah - Sambow, Jessica P.; Luas, Luosje Treesje (Educatio Christi, 2024)
This research discusses teenagers who experience the impact of divorce. Divorce is the end of a relationship between a husband and wife who are unable to maintain the integrity of the household. And the people who have the biggest impact on divorce cases are the children. Children are victims of the divorce that occurs. This research is intended to determine the impact of divorce on teenagers and appropriate pastoral care for teenagers in the GMIM Kingdom of Allah Lolah Congregation, Tanawangko I Region. This research uses a qualitative research method with a case study method with direct interviews with informants. The results of this research indicate that adolescent victims of divorce must be accompanied and receive continuous pastoral care. This is because teenage victims of divorce feel deep trauma regarding divorce, so they need to receive pastoral assistance.